Modification of the Associations Between Duration of Oral Contraceptive Use and Ovarian, Endometrial, Breast, and Colorectal Cancers - Michels, Kara A. (JAMA Oncol, 2018)
IMPORTANCE: Although oral contraceptive (OC) use is common, the influence of OC use on carcinogenesis is not fully understood. A recent Agency for Healthcare Research and Quality report identified a need to understand the consistency of OC use and cancer associations across subpopulations, including smokers and obese women. OBJECTIVE: To determine whether associations between duration of OC use and risk of specific cancers were modified by lifestyle characteristics. DESIGN, SETTING, AND PARTICIPANTS: The prospective NIH-AARP Diet and Health Study (enrolled 1995-1996, followed until 2011), with population-based recruitment of AARP members in 6 states and 2 metropolitan areas. All analyses included at least 100 000 women who reported OC use at enrollment. We identified 1241 ovarian, 2337 endometrial, 11 114 breast, and 3507 colorectal cancer cases during follow-up. Data analysis was performed between September 2016 and April 2017. EXPOSURES: Duration of OC use (never or <1 year [reference], 1-4, 5-9, or ≥10 years). MAIN OUTCOMES AND MEASURES: Development of ovarian, endometrial, breast, and colorectal cancers. We examined effect modification by modifiable lifestyle characteristics: cigarette smoking, alcohol consumption, body mass index (BMI), and physical activity. We used Cox models adjusted for age, race, age at menarche, and the modifiers of interest. RESULTS: The analytic population was aged 50 to 71 years (median, 62 years) at enrollment and largely white (91%) and postmenopausal (96%). For ovarian cancer, OC use–associated risk reductions strengthened with duration of use (long-term OC use [≥10 years] HR, 0.60; 95% CI, 0.47-0.76; P < .001 for trend) and were similar across modifiable lifestyle factors. Risk reductions for endometrial cancer strengthened with duration of use (long-term OC use HR, 0.66; 95% CI, 0.56-0.78; P < .001 for trend); the most pronounced reductions were among long-term OC users who were smokers (HR, 0.47; 95% CI, 0.25-0.88), had obese BMIs (0.36; 95% CI, 0.25-0.52), and who exercised rarely (HR, 0.40; 95% CI, 0.29-0.56). Associations between OC use and breast and colorectal cancers were predominantly null. CONCLUSIONS AND RELEVANCE: Long-term OC use is consistently associated with reduced ovarian cancer risk across lifestyle factors. We observed the greatest risk reductions for endometrial cancer among women at risk for chronic diseases (ie, smokers, obese BMI). Oral contraceptive use may be beneficial for chemoprevention for a range of women with differing baseline cancer risks.